Experimental study of a three-storey concrete frame structure with smooth bars under cyclic lateral loading - Palios, Xenofontas; Strepelias, Elias; Stathas, Nikolaos; Fardis, Michael N.; Bousias, Stathis N.; Chrysostomou, Christis; Kyriakides, Nicholas (My University, 2020)
Past lateral cyclic or seismic tests of concrete frames with smooth bars in columns are very few and limited as far as the test structure’s size and geometry are concerned; moreover, they have not focused on the effect of detailing and lap-splicing of such bars on local and global behaviour. To help fill this knowledge gap with new data, the paper presents the cyclic lateral load test of a 2:3-scale three-storey, one-by-two-bay, strong beam-weak column RC frame, focusing on the effects of the column’s smooth bars and of their detailing on local and global behaviour. Slippage of bars caused concentration of column deformations in flexural cracks at the top and base sections and gave to the global hysteresis loops a shape typical of bond-slip behaviour, but without cyclic strength decay. Despite chord rotation demands of up to 0.055 rads and storey drifts of almost 5%, damage was limited and had nothing to do with the use of smooth bars in the columns. Despite the important role of bar slippage for the response, bar strains show that wherever the surrounding concrete was in compression, column bars were in compression as well. Lap splices at and/or FRP wrapping of column end regions did not have systematic effects on column behaviour. Overall, no adverse effect of the use of smooth bars was identified.
Keywords: Cyclic loading; Existing structures; Plain bars; Retrofitting reinforced concrete structures